STRUCTURE AND DIELECTRIC PROPERTIES OF SURFACE SNOW ALONG THE TRAVERSE ROUTE FROM COAST TO DOME FUJI STATION, QUEEN MAUD LAND, ANTARCTICA - シライワ, タカユキ; ショウジ, ヒトシ; サイトウ, タカシ; ヨコヤマ, コタロウ; ワタナベ, オキツグ; SHIRAIWA, Takayuki; SHOJI, Hitoshi; SAITO, Takashi; YOKOYAMA, Kotaro; WATANABE, Okitsugu (National Institute of Polar Research, 1996)
P(論文) Stratigraphical observations were carried out on the surface snow from the coast to the ice divide, Dome Fuji Station, in the summer of 1994/1995,to provide microwave remote sensing with ground truth data. Stratification, grain size and dielectric properties were measured in 1m-deep snow pits excavated every 30-40km of the 1000km-long Dome Fuji Station traverse route. There exist three regional characteristics in the altitudinal distribution of the averaged real part of the dielectric constant ε′ : a constant value in the coastal region, a higher value in the intermediate region, and a gradual decrease in the higher region. According to the measured snow properties indispensable to the utilization of microwave remote sensing, the dry snow zone of the studied area is divided into three parts : a region of compacted snow and solid-type depth hoar (1000 to 2000/2300m a.s.l.), where spatial and vertical distribution of various snow properties are uniform; a region of wind-packed snow and skeleton-type depth hoar (2000/2300 to 3500m), which is characterized by spatial alteration of the glazed surface and the stratified depth hoar layer; a region of interbedded skeleton-and solid-types depth hoar (higher than 3500m) where the seasonal stratification of snow is characterized by thin-hard summer and thick-soft winter layers. departmental bulletin paper